2001
DOI: 10.1161/01.atv.21.6.1053
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis of LDL by Human Secretory Phospholipase A 2 Induces Particle Fusion and Enhances the Retention of LDL to Human Aortic Proteoglycans

Abstract: Abstract-The first morphological sign of atherogenesis is the accumulation of extracellular lipid droplets in the proteoglycan-rich subendothelial layer of the arterial intima. Secretory nonpancreatic phospholipase A 2 (snpPLA 2 ), an enzyme capable of lipolyzing LDL particles, is found in the arterial extracellular matrix and in contact with the extracellular lipid droplets. We have recently shown that in the presence of heparin, lipolysis of LDL with bee venom PLA 2 induces aggregation and fusion of the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 58 publications
1
90
0
Order By: Relevance
“…Previous studies have shown that lipolysis of LDL with sPLA 2 results in an increased affinity for proteoglycans secreted by human arterial smooth muscle cells (47) and proteoglycans isolated from human aorta (20). In a recent study, Flood et al (24) identified the molecular basis for this altered interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that lipolysis of LDL with sPLA 2 results in an increased affinity for proteoglycans secreted by human arterial smooth muscle cells (47) and proteoglycans isolated from human aorta (20). In a recent study, Flood et al (24) identified the molecular basis for this altered interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that sPLA 2 hydrolysis of LDL-PL results in structural alterations of the particles that promote lipid accumulation in the vessel wall and enhances macrophage uptake. Hydrolysis of LDL by sPLA 2 in vitro results in an increased affinity for proteoglycans, which would be expected to increase retention in the subendothelium (20,21). Lipolysis of LDL by sPLA 2 leads to conformational changes in apoB-100 and reorganization of lipids that induce particle aggregation (22)(23)(24).…”
mentioning
confidence: 99%
“…The degree of aggregation and/or fusion of proteolyzed [ 3 H]cholesteryl linoleate-labeled LDL was determined by rate zonal ultracentrifugation (37), as described previously (38). Briefly, a linear NaBr gradient (d ϭ 1.006 -1.10 g/ml) was layered on top of 50-l samples of modified [ 3 H]cholesteryl linoleate-LDL in 250 l of 40% NaBr (w/v) and centrifuged at 33,000 rpm in a SW 40 Ti rotor (Beckman) for 1 h at 20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Secretory PLA2, is stored in the secretory granules of immune cells such as leukocytes and mast cells and participates in arachidonic acid metabolism during the progression of inflammation. 18,19 High concentrations of sPLA2 are found in inflammatory exudate. 20 Presently, expression of sPLA2 is thought to be promoted by IL-1, as well as by inflammatory cytokines such as interferon and IL-6, lipopolysaccharides, and substances that elevate intracellular concentrations of cyclic adenosine monophos- phate, such as forskolin.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recent interest has focused on secretory group IIA phospholipase A2 (sPLA2) because of its potential role in the accumulation of oxidized LDL in vascular walls as well as in the progression of atherosclerosis and the development of CAD. [17][18][19][20] The value of sPLA2 as a potential marker for the risk of cardiovascular events has received considerable attention.…”
mentioning
confidence: 99%